2017
DOI: 10.1002/anie.201708561
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of 3β‐Hydroxy‐7β‐kemp‐8(9)‐en‐6‐one, a Diterpene Isolated from Higher Termites

Abstract: The first total synthesis of the title diterpene was accomplished starting from the Wieland-Miescher ketone. A diastereoselective sulfa-Michael addition enabled the generation of the delicate β,γ-unsaturated ketone moiety, while the tetracyclic kempane skeleton was readily constructed through domino metathesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Metz and coworkers found use of our method for the synthesis of 3β-hydroxy-7β-kemp-8(9)-en-6-one. 35 In contrast, rhodium-catalyzed isomerization leads to the conjugated olefin. 36…”
Section: Isomerization Cycloisomerization and Retrocycloisomerizationmentioning
confidence: 99%
“…Metz and coworkers found use of our method for the synthesis of 3β-hydroxy-7β-kemp-8(9)-en-6-one. 35 In contrast, rhodium-catalyzed isomerization leads to the conjugated olefin. 36…”
Section: Isomerization Cycloisomerization and Retrocycloisomerizationmentioning
confidence: 99%
“…In contrast to the long multistep approaches reported by Paquette and Deslongchamps for the construction of the tetracyclic core of these terpenes, 185 Metz and co-workers reported the preparation of this polycyclic system in one step and in excellent yield from the dienyne 362 (Scheme 44), which was prepared from the Wieland-Miescher ketone in 20 steps. 186 Thus, exposure of 362 to the Grubbs II catalyst (4) afforded the tetracyclic de-rivative 363 in an astonishing 97% yield. Whereas the reduction of the resulting tetracyclic ketone 363 with L-Selectride provided the alcohol 364 with the opposite stereochemistry to that of the natural product, reduction of the bicyclic ketone precursor 362 provided the correct diastereomer 365 under the same reduction conditions.…”
Section: Scheme 43 Total Synthesis Of Englerin Amentioning
confidence: 99%
“…In 2017, Metz's group (Wang Y. et al, 2017) reported the first total synthesis of 3β-hydroxy-7β-kemp-8(9)-en-6-one, a diterpene with 5/6/6/7-fused tetracyclic kempane scaffold ( Figure 2A). The key step of this synthesis is a domino RCM from a dienyne-tethered Wieland-Miescher ketone using Grubbs II catalyst, which enables one-pot construction of two fused rings.…”
Section: Construction Of Polycyclic Carbocyclesmentioning
confidence: 99%